The effect of an educational program using aids in the development of some motor abilities and learning of the two skills jumping to for your men’s Technical gymnastics. - Altememi, Haydar (Journal of Physical Education, 2018)
The effect of an educational program using aids in the development of some motor abilities and learning of the two skills jumping to for your men’s Technical gymnastics. Objective of the study: Learn about the effect of the use of some aids in learning the skills of jumping and locking on the table of the technical gymnastic jumping table. The two researchers used the study program on a sample of (30) students from the third stage in the Faculty of Physical Education University of Misan, divided into two experimental groups (theoretical science branch) and an officer (Applied Science Branch) with (15) students per group and (2) The program has been used for 12 weeks and 2 units per week for each group. The researcher used the principle of progress in teaching my skill in search of landing on the jumping horse and getting out of it with a proper landing. , Where he initially used a different horse apparatus for height and spandex The two groups (60) were given an attempt to use sponges without a device, and then the device was placed between the legs and from many attempts the group exceeded the element of fear and anxiety. The research included the most important aspects of learning, movement and skill were chosen through the distribution of questionnaires to experts with expertise and experience number (13) expert. The most important results of the research proved the effectiveness of the use of aids in teaching my skills in the research on the jump table, which helps to learn the skills better and had a positive impact in raising the level of performance for students by removing the factor of fear and frequency of injury and thus raise the level Performance of students in practical lectures